Technical and economic feasibility of a small vertical axis wind turbine in low wind conditions compared to other power sources for pumping water - Testi, Andrei [UNESP]; Souza, Teofilo Miguel de [UNESP]; Trannin, Isabel Cristina de Barros [UNESP] (Elsevier, 2024)
In a global context, the significance of transitioning to renewable energy sources is paramount for sustainable development. This relevance is particularly evident in Brazil, where significant strides have been made in microgeneration of photovoltaic solar power and on-shore large-scale horizontal-axis wind power. Despite the country's extensive energy capacity from hydroelectric facilities, still approximately 38.5 million people reside in rural areas and surrounding areas, emphasizing the need for effective and affordable energy solutions for these regions. Based on this social and business opportunity of small-sized devices used in sustainable development, this practical experimentation explores the viability of initial studies from a prototyped small vertical-axis wind turbine (VAWT) system for water pumping, comparing its technical and economic feasibility with commercial off-the-shelf (COTS) photovoltaic solar pump (PV) and conventional electrical pump systems (EP). Two scenarios are investigated: (1) a patented transmission mechanism connected to a double effect pump and (2) the VAWT system designed to be connected to the same mechanism. Compared to PV ‘systems, scenario (1) offers 1.4x higher flowrate at a significantly lower cost (137% less) and consumes half the power. It offers a lower flowrate (2.6x) than EP systems but at a lower cost (36% less) and consumes one-third the power. Scenario (2) provides 2.7x less water flow than PV at a slightly lower cost (41% less). While less efficient in water flow (10 x) compared to EP, it has a slightly higher cost (15% more). This research builds upon existing knowledge and offers valuable insights for future small VAWT applications in low-wind remote areas for water pumping.
Keywords: Electrical pump; Low-cost pumping system; Photovoltaic solar pump; Renewable energy; Vertical axis wind turbine; Water pump